2005
DOI: 10.1200/jco.2005.01.2781
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Gemcitabine Plus Carboplatin Versus Single-Agent Gemcitabine in the Treatment of Locally Advanced or Metastatic Non–Small-Cell Lung Cancer: The Swedish Lung Cancer Study Group

Abstract: In advanced NSCLC, gemcitabine/carboplatin therapy resulted in significant survival benefit compared with single-agent gemcitabine without undue increase in toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 22 publications
11
74
3
1
Order By: Relevance
“…For vinorelbine/platinum combinations, recent phase III studies have yielded median survival data ranging from 6.5 to 11 months (Wozniak et al, 1998;Kelly et al, 2001;Scagliotti et al, 2002;Fossella et al, 2003;Gebbia et al, 2003;Georgoulias et al, 2005;Martoni et al, 2005;Tan et al, 2005;Plessen et al, 2006). In the gemcitabine/platinum metaanalysis (Le Chevalier et al, 2005), median survival in the gemcitabine group was 9 months, reflecting the mean value for a number of studies (Le Chevalier et al, 1994;Cardenal et al, 1999;Sandler et al, 2000;Scagliotti et al, 2002;Schiller et al, 2002;Alberola et al, 2003;Gebbia et al, 2003;Smit et al, 2003;Zatloukal et al, 2003;Martoni et al, 2005;Rudd et al, 2005;Sederholm et al, 2005). Our shorter median survival is possibly explained by the high proportion of patients with PS 2 (28%), which is the most powerful predictor of survival in NSCLC patients (Stanley, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…For vinorelbine/platinum combinations, recent phase III studies have yielded median survival data ranging from 6.5 to 11 months (Wozniak et al, 1998;Kelly et al, 2001;Scagliotti et al, 2002;Fossella et al, 2003;Gebbia et al, 2003;Georgoulias et al, 2005;Martoni et al, 2005;Tan et al, 2005;Plessen et al, 2006). In the gemcitabine/platinum metaanalysis (Le Chevalier et al, 2005), median survival in the gemcitabine group was 9 months, reflecting the mean value for a number of studies (Le Chevalier et al, 1994;Cardenal et al, 1999;Sandler et al, 2000;Scagliotti et al, 2002;Schiller et al, 2002;Alberola et al, 2003;Gebbia et al, 2003;Smit et al, 2003;Zatloukal et al, 2003;Martoni et al, 2005;Rudd et al, 2005;Sederholm et al, 2005). Our shorter median survival is possibly explained by the high proportion of patients with PS 2 (28%), which is the most powerful predictor of survival in NSCLC patients (Stanley, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…To improve therapeutic efficacy, retrospective subgroup analyses of several phase III trials have investigated platinum-based treatment for elderly patients with advanced NSCLC (Kelly et al, 2001;Langer et al, 2002;Hensing et al, 2003;Belani et al, 2005;Sederholm et al, 2005;Ansari et al, 2007). In these studies were indicated that PFS OS, and response rate were not significantly superior between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies were indicated that PFS OS, and response rate were not significantly superior between age groups. Grade 3-4 toxicities for elderly patients, some studies were higher (Langer et al, 2002;Belani et al, 2005;Sederholm et al, 2005;Ansari et al, 2007), whereas others were not observed (Kelly K et al, 2001;Hensing et al, 2003). We performed a retrospective analysis of the efficacy and side effects of cisplatin-based therapy for the treatment of elderly patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has subsequently been discarded. A comparison of platinum-based two-drug combinations with novel single-agent therapy demonstrated higher survival and response rates with the combination [34,35]. Thus, two-drug combinations form the foundation of systemic therapy for NSCLC.…”
Section: Strategies To Improve the Efficacy Of Systemic Chemotherapymentioning
confidence: 99%